Peran Kewirausahaan dalam Membangun dan Memajukan Perekonomian Bangsa - Suwandi Suwandi; Amelia Amelia; Mela Safitri Situmorang; Sholeh Parlindungan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This article discusses the role of entrepreneurship in building and advancing the nation's economy. This article also reviews the relationship and role of entrepreneurship in the nation's economic development. Entrepreneurship has its own role in the nation's economic growth, namely increasing productivity. Entrepreneurship also influences economic development in Indonesia. The current economic problems in Indonesia are endlessly discussed, sometimes they rise and sometimes they fall very far. However, entrepreneurship will help the economy in Indonesia. The aim of this research is to find out how much entrepreneurship plays a role in building and advancing the nation's economy. This research uses a qualitative method where the data collection process uses library research. The results of this research show that entrepreneurship also plays a role in encouraging the economic activities of families, communities, and the nation's economy . The dynamics of business activities can encourage economic growth and improve community welfare.